The effect of alternative measures of distance on the correlation of real effective exchange rate returns: An approach to contagion analysis - Jean Coulom; Vijay Shenai (International Journal of Financial Studies, 2018)
The topic of contagion has gained importance in the last few decades, earning its place amongst the most debated topics in international economics. Contagion is a phenomenon where market disturbances in crisis times are observed to spread from one country to the other in the form of comovements in exchange rates, stock prices, bond spreads, capital and trade flows. Analysing contagion and, more important, being able to make an on-coming prediction successfully helps economic planners to take appropriate rectificatory action toward establishing stable macroeconomic conditions. In previous studies, various proxies for distance have been used to test their explanatory power on a suitable dependent variable, typically a crisis index. In this paper, the separate impacts of geographic distance, psychic distance and cultural factors are tested on the correlation of real exchange rate returns to assess their predictive power. Using a sample of 30 countries for a period of 24 years (1993 to 2016) and data at monthly intervals, a panel regression is conducted. The findings of the analysis are that there is a negative effect of all the three explanatory variables on the correlation of real exchange rate returns. Moreover, a rolling regression conducted across the whole period shows coefficients going back to zero just before a crisis event and tending to fall afterwards. These findings contribute to the literature on contagion analysis by taking a different approach and exploring the separate impacts of geographic distance, psychic distance and cultural factors as explanatory variables and assessing their predictive power. The findings of the research are thus useful for policy makers towards restoring stable economic conditions.
Keywords: F32; F41; O19; 330; financial crises; contagion; open economy macroeconomics